RIPK3 and Caspase-1/11 Are Necessary for Optimal Antigen-Specific CD8 T Cell Response Elicited by Genetically Modified Listeria monocytogenes - Rana, Aamir; de Almeida, Felipe Campos; Paico Montero, Henry A.; Gonzales Carazas, Maryanne M.; Bortoluci, Karina R.; Sad, Subash; Amarante-Mendes, Gustavo P. (Frontiers in Immunology, 2020)
Efficient induction of effector and long-term protective antigen-specific CD8+ T memory response by vaccination is essential to eliminate malignant and pathogen-infected cells. Intracellular infectious bacteria, including Listeria monocytogenes, have been considered potent vectors to carry multiple therapeutic proteins and generate antigen-specific CD8+ T cell responses. Although the role of molecules involved in inflammatory cell death pathways, such as necroptosis (RIPK3-mediated) and pyroptosis (Caspase-1/11-mediated), as effectors of immune response against intracellular bacteria are relatively well understood, their contribution to the adjuvant effect of recombinant bacterial vectors in the context of antigen-specific CD8+ T cell response remained obscure. Therefore, we evaluated the impact of RIPK3 and Caspase-1/11 (Casp-1/11) individual and combined deficiencies on the modulation of antigen-specific CD8+ T cell response during vaccination of mice with ovalbumin-expressing Listeria monocytogenes (LM-OVA). We observed that Casp-1/11 but not RIPK3 deficiency negatively impacts the capacity of mice to clear LM-OVA. Importantly, both RIPK3 and Casp-1/11 are necessary for optimal LM-OVA-mediated antigen-specific CD8+ T cell response, as measured by in vivo antigen-specific CD8+ T cell proliferation, target cell elimination and cytokine production. Furthermore, Casp-1/11 and Casp-1/11/RIPK3 combined deficiencies restrict the early initiation of antigen-specific CD8+ T cell memory response. Taken together, our findings demonstrate that RIPK3 and Casp-1/11 influence the quality of CD8+ T cell responses induced by recombinant L. monocytogenes vectors.